2009
DOI: 10.1245/s10434-008-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Pain Palliation in Patients with Bone Metastases Using MR-Guided Focused Ultrasound Surgery: A Multicenter Study

Abstract: The results suggest that MRgFUS has the ability to provide an accurate, effective, and safe noninvasive palliative treatment for patients with bone metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
197
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(204 citation statements)
references
References 36 publications
7
197
0
Order By: Relevance
“…This provides an improved safety profile by reducing thermal damage around the treated bone site [19][20][21].…”
Section: High-intensity Focused Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides an improved safety profile by reducing thermal damage around the treated bone site [19][20][21].…”
Section: High-intensity Focused Ultrasoundmentioning
confidence: 99%
“…Liberman et al in 2009 published the first multicenter clinical study on the use of FUS for pain palliation of bone metastases [21]. This report includes previous pioneer work from [18] and [20], comprising 31 patients and 32 bone lesions.…”
Section: Metastatic Bone Tumorsmentioning
confidence: 99%
“…This technology is a noninvasive treatment modality that is FDA-approved for the treatment of uterine fibroids and bone metastasis. Several studies have demonstrated that focused ultrasound ablation can cause regression of uterine fibroids and alleviate pain from bone metastasis [12,15,20]. MRgFUS may also be useful in the treatment of extremity soft tissue tumors; however, investigations for this application have not to our knowledge been published.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, external-beam radiation cannot reach the dose for killing the bone tumor because of nearby vital organs. Previously, multiple minimally invasive imageguided ablation strategies have been studied as treatments for painful bone metastases [23,24]. Cryoablation and RF ablation have been the most studied techniques demonstrating significantly reduced pain in patients who are unresponsive or incompletely responsive to standard conventional therapies.…”
Section: Discussionmentioning
confidence: 99%